Value-based Customers Satisfaction and Continuance Intention for Mobile Financial Services: the roles of Utilitarian, Hedonic, and Personal Values - N. O. Omigie (International Telecommunications Society (ITS), 2017)
“M-PESA” mobile financial service has remained a dominate player in the Kenya financial service market. This study presents a conceptual research model that is grounded in means-end theory. It connects customer value hierarchy to customer attitudes and post-adoption outcomes behavior. It aims to investigate the impacts of customer value in a hierarchical order on customer satisfaction and continuance use intention. When empirically validated, it will present a value-based framework for examining the influences of customer value on customer attitudes and behavior. The model presents both theoretical and practical implications for both academia and MFS providers and marketing managers.
Keywords: 330; MFS; M-PESA; means-end theory; customer value hierarchy; utilitarian value; hedonic value; personal values